Exploring food choices among educated adults in the United Arab Emirates - Zidan, Souzan; Hilary, Serene; Platat, Carine (Frontiers in Nutrition, 2026)
IntroductionUnderstanding food choice motives (FCMs) is crucial to designing dietary interventions to improve human health and environmental sustainability. This study aims to explore FCMs and to identify whether sociodemographic and anthropometric characteristics influence these motives among educated adults.MethodsThis cross-sectional study surveyed 894 respondents between May 2023 and September 2024 at the United Arab Emirates University. The online questionnaire gathered self-reported information on sociodemographic characteristics, body weight and height, and self-reported knowledge of dietary guidelines. The FCMs were assessed using the adapted English and Arabic versions of the Food Choice Questionnaire (FCQ), covering nine domains: convenience, mood, health, natural content, familiarity, weight control, eco-ethics and price. Mann–Whitney U and Kruskal-Wallis tests were used to compare differences in food choice motivation among educated adults with different sociodemographic and anthropometric characteristics. Further analysis was done using linear regression to determine the association between sociodemographic and anthropometric characteristics (age, BMI, sex, nationality, marital status, family size, educational level, employment status, monthly income, diet counselling, nutrition education, and knowledge of dietary guidelines) and FCMs.ResultsThis study found that sensory appeal was the most important motive. In contrast, eco-ethics and familiarity were ranked as the least important. There was a statistically significant difference in FCMs among educated adults according to their sociodemographic and anthropometric characteristics (p < 0.05). Overall, only a small proportion of FCMs were affected by participants’ characteristics (3.9–12.6%). Sex was most often linked with variations in FCMs (i.e., all FCMs except for price were significantly more important to females than males; p < 0.05).ConclusionMultiple motivations could determine people’s food choices. Eco-ethics and familiarity were the least important motives, suggesting that environmental and ethical concerns are not prioritized in food decisions. Our results also indicate that educated adults might be open to trying novel foods, which may support the introduction of more sustainable food choices. Moreover, sociodemographic and anthropometric factors had a limited role in influencing FCMs among educated adults, with the largest differences observed between males and females. Our findings also suggest that future dietary interventions targeting educated adults should be tailored to their sensory preferences.